2020
DOI: 10.1177/0963689720931433
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: OTUB2 Promotes Homologous Recombination Repair Through Stimulating Rad51 Expression in Endometrial Cancer

Abstract: Genetic instability, raised from dysregulation of DNA repair, is involved in tumor development. OTUB2 (ovarian tumor domain protease domain-containing ubiquitin aldehyde-binding protein 2), which is responsible for DNA double-strand break (DSB), is implicated in carcinogenesis of various tumors. The effect of OTUB2 on endometrial cancer progression was then investigated. First, OTUB2 was found to be upregulated in endometrial cancer tissues and cell lines, and was closely associated with overall survival of en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…It has also been reported that OTUB2 promotes homologous recombination repair of endometrial carcinoma through YAP/TAZ mediated Rad51 expression, which provides a potential therapeutic target for endometrial carcinoma. Silencing of OTUB2 can inhibit the growth of endometrial cancer and increases the sensitivity of tumor to anti-tumor drugs [ 8 ]. In the HCC cell line, knocking-down OTUB2 expression can significantly inhibit the growth of liver cancer cells [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has also been reported that OTUB2 promotes homologous recombination repair of endometrial carcinoma through YAP/TAZ mediated Rad51 expression, which provides a potential therapeutic target for endometrial carcinoma. Silencing of OTUB2 can inhibit the growth of endometrial cancer and increases the sensitivity of tumor to anti-tumor drugs [ 8 ]. In the HCC cell line, knocking-down OTUB2 expression can significantly inhibit the growth of liver cancer cells [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…OTUB2 is a dihydroubiquitase, a member of the ovarian tumor domain (OTU) family with effects on various biological activities of the body [ 3 , 4 ]. Some researchers have found that OTUB2 promotes the development of breast cancer [ 5 ], non-small cell lung cancer [ 6 ], thyroid papilloma cancer [ 7 ], endometrial cancer [ 8 ], and liver cancer [ 9 ]. Yes-associated protein (YAP1) and transcriptional co-activator with PDZ-binding motif (TAZ) are core factors located downstream of the Hippo signaling pathway.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, OTUB2, as an intermediate molecule, both undertakes the downstream effects of RAS mutations and triggers YAP/TAZ-mediated oncogene expression based on its deubiquitination function (K48), forming a chain reaction and worsening cancer progression. On this basis, the overexpression of recombination protein A (Rad51) in endometrial cancer is a representative example of YAP/TAZ-mediated gene expression ( Wan et al, 2020 ). The up-regulation of Rad51 protein can not only lead to drug resistance of cancer cells but also promote cell growth and proliferation ( Klein, 2008 ; Chen et al, 2017 ).…”
Section: The Relationship Between Otub2 and Diseasesmentioning
confidence: 99%
“…Similarly, overexpression of OTUB2 in endometrial carcinoma can indirectly increase Rad51 expression by interacting with YAP/TAZ to promote HR ( Wan et al, 2020 ). However, this HR in endometrial cancer tissues seems to be pathological ( Wan et al, 2020 ).…”
Section: The Relationship Between Otub2 and Diseasesmentioning
confidence: 99%
See 1 more Smart Citation